An Overview of Bioactive Alkaloid, Semi-Synthetic Analogs, Mechanism of Action and Structure-Activity Relationship of Piperine as Antioxidant - Joshi, Sagar; Kumar , Rajnish; Sharma, Divya (Asian Journal of Chemistry, 2021)
Piperine, a natural alkaloid obtained from black pepper exhibit a variety of pharmacological activities like antioxidant activity and in this article, the mechanism of the antioxidant, structure-activity relationship of piperine as an antioxidant and various schemes of derivatives of piperine as antioxidants were discussed.